2020
DOI: 10.1088/2053-1583/ab8919
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol-jet-printed graphene electrochemical histamine sensors for food safety monitoring

Abstract: Carbon nanomaterials such as graphene exhibit unique material properties such as high electrical conductivity, surface area, and biocompatibility that have the potential to significantly improve the performance of electrochemical sensors. Since in-field electrochemical sensors are typically disposable, they require materials that are amenable to low-cost, high-throughput, and scalable manufacturing. Conventional graphene devices based on low-yield chemical vapor deposition techniques are too expensive for such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 103 publications
0
61
0
Order By: Relevance
“…Apart from this, recent work has demonstrated AJP can be used to detect glucose, cytokines, proteins, and histamine. [ 21,280–282 ] Electrodes with trace widths as low as 15 µm can be achieved, and as expected, both the printing speed and number of deposited layers affect the dimensions of the traces, and consequently the electrochemical properties. [ 283 ] These studies demonstrate that AJP is a versatile AM technology, capable of achieving high resolution electrodes with complex geometries.…”
Section: Additive Manufacturing Of Ec Biosensorsmentioning
confidence: 73%
“…Apart from this, recent work has demonstrated AJP can be used to detect glucose, cytokines, proteins, and histamine. [ 21,280–282 ] Electrodes with trace widths as low as 15 µm can be achieved, and as expected, both the printing speed and number of deposited layers affect the dimensions of the traces, and consequently the electrochemical properties. [ 283 ] These studies demonstrate that AJP is a versatile AM technology, capable of achieving high resolution electrodes with complex geometries.…”
Section: Additive Manufacturing Of Ec Biosensorsmentioning
confidence: 73%
“…During an aerosol jet printing (AJP) process, the ink is atomized through a pneumatic or ultrasonic mechanism and directed to the substrate by a sheath gas flow. [ 558–561 ] The AJP process is compatible with a wide range of ink viscosity and can be applied to print functional materials on various substrates. [ 562,563 ] For example, Parate et al [ 560 ] demonstrated the AJP fabrication of a graphene‐based field electrochemical histamine sensor.…”
Section: Device Fabrication and Integration For 2d Materials‐based Wearable Sensorsmentioning
confidence: 99%
“…Tuna sh His Chemical sensor using aerosol -jet -printed graphene 3.1 x 10 −5 (Parate et al, 2020) Marine sh His Amperometric biosensor using diamine oxidase and peroxidase as molecular recognition element Not de ned (Trevisani et al, 2017) Food products Voltammetric sensor based on molecularly imprinted polymer (MIP) 7.4 x 10 −11 (Akhoundian et al, 2017) Chicken meat Put, Cad, Tyr Amperometric biosensor using pea seedling amine oxidase (PSAO) as molecular recognition element 1.2-4.5 x 10 −5 Telsnig et al…”
Section: Food Samplementioning
confidence: 99%